Cytokinin Activity of cis-Zeatin and Phenotypic Alterations Induced by Overexpression of Putative cis-Zeatin-O-glucosyltransferase in Rice(1)([C])([W])([OA]) - Kudo, Toru (American Society of Plant Biologists, 2012)
cis-Zeatin (cZ) is generally regarded as a cytokinin with little or no activity, compared with the highly active trans-zeatin (tZ). Although recent studies suggested possible roles for cZ, its physiological significance remains unclear. In our studies with rice (Oryza sativa), cZ inhibited seminal root elongation and up-regulated cytokinin-inducible genes, and its activities were comparable to those of tZ. Tracer experiments showed that exogenously supplied cZ-riboside was mainly converted into cZ derivatives but scarcely into tZ derivatives, indicating that isomerizations of cZ derivatives into tZ derivatives are a minor pathway in rice cytokinin metabolism. We identified three putative cZ-O-glucosyltransferases (cZOGT1, cZOGT2, and cZOGT3) in rice. The cZOGTs preferentially catalyzed O-glucosylation of cZ and cZ-riboside rather than tZ and tZ-riboside in vitro. Transgenic rice lines ectopically overexpressing the cZOGT1 and cZOGT2 genes exhibited short-shoot phenotypes, delay of leaf senescence, and decrease in crown root number, while cZOGT3 overexpressor lines did not show shortened shoots. These results propose that cZ activity has a physiological impact on the growth and development of rice.